Aplikasi Pencarian Informasi Sholat Jumat di Kota Bandar Lampung Menggunakan LBS Berbasis Android - Kurnia Muludi; Febi Eka Febriansyah; Alfabet Setiawan (Jurnal Komputasi, 2016)
The utilization of GPS (Global Positioning System) technology on telecommunication tools stimulates Location Based Service (LBS) in smartphone.Â  This service provides an information that can be accessed through mobile network and is able to use geographic location. In this research, application is designed and created for giving the information about Friday prayer schedule in Bandar Lampung, including the information about mosques, preacher in charge in certain mosque, and shows the nearest mosque location within a radius of 1 km. The application consists of Android Mobile application for users and Web Based System for Administrator and both are connected with Web Service. This study shows that the new created application can give the information about Friday prayer in Bandar Lampung and the test result by using Black-Box equivalence partitioning shows that the application runs in accordance with the requirements.